(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the intricacies of American English pronunciation standards, offering a detailed exploration of its historical evolution, key linguistic features, regional variations, and global influence. The article elucidates the distinctive elements of American English pronunciation, such as vowel sounds, consonant modifications, stress patterns, and regional accents, providing valuable insights for both language learners and enthusiasts. It emphasizes the impact of American media on the dissemination of this pronunciation standard worldwide, highlighting its significance in cross-cultural communication. Moreover, the article encourages learners to engage with native speakers, diverse resources, and various accents to enhance their proficiency in American English pronunciation. Overall, this annotation recognizes the article’s comprehensive coverage and its importance in elucidating the nuances and prominence of American-based pronunciation standards within the global linguistic landscape.